Evolutionary drivers of group foraging: A new framework for investigating variance in food intake and reproduction. (2nd September 2019) - Grinsted, Lena; Deutsch, Ella K.; Jimenez‐Tenorio, Manuel; Lubin, Yael
Abstract: A proposed fundamental driver of group living is more reliable, predictable foraging and reproduction, i.e., reduced variance in food intake and reproductive output. However, existing theories on variance reduction in group foraging are simplistic, refer to variance at the level of individuals and groups without linking the two, and do not spell out crucial underlying assumptions. We provide a new, widely applicable framework for identifying when variance reduction conveys fitness benefits of group foraging in a wide range of organisms. We discuss critical limitations of established theories, the Central Limit Theorem and Risk‐Sensitive Foraging Theory applied to group foraging, and incorporate them into our framework while addressing the confusion over the levels of variance and identifying previously unaddressed assumptions. Through a field study on colonial spiders, Cyrtophora citricola, we demonstrate the importance of evaluating the level of food sharing as a critical first step, previously overlooked in the literature. We conclude that variance reduction provides selective advantages only under narrow conditions and does not provide a universal benefit to group foraging as previously proposed. Our framework provides an important tool for identifying evolutionary drivers of group foraging and understanding the role of fitness variance in the evolution of group living.